Pengaruh Aplikasi Tiktok terhadap Perilaku Sosial Siswa dalam Pembelajaran Kelas 4 SDIT Al Ibrohimi Gresik - Virdausah Septtiarini; Arya Setya Nugroho; Afakhrul Masub Bachtiar (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examined the impact of TikTok application usage on the social behavior of fourth-grade students at SDIT Al Ibrohimi Gresik. A quasi-experimental design was employed involving two classes: Class IV-A as the control group, which received conventional learning, and Class IV-B as the experimental group, which participated in TikTok-assisted learning. Both groups implemented the Project-Based Learning (PBL) model. A pre-test and post-test were administered to assess students’ social behavior, covering communication, cooperation, responsibility, and self-confidence. Data were collected using questionnaires and observation sheets and analyzed through Paired Sample t-Test and Independent Sample t-Test. The experimental group’s mean score increased from 81.00 on the pre-test to 84.33 on the post-test, while the control group improved slightly from 77.32 to 78.92. The Paired Sample t-Test indicated a significant improvement in the experimental group (p = 0.036 < 0.05), demonstrating the positive effect of TikTok-assisted learning on students’ social behavior. The Independent Sample t-Test also showed a significant difference between the experimental and control groups (p = 0.036). These findings suggest that integrating TikTok into PBL effectively enhances students’ social behavior, particularly in communication, collaboration, and self-confidence.